“Aplicación móvil para la detección y medición de altura en plantas de maíz utilizando DEEP LEARNING” - Caiza Caiza, Kevin Stalin (2020)
The purpose of this research project is to use Deep Learning algorithms for the detection of objects in images. In this case two classes were automatically detected: maize and not maize. Once one of the two classes in the image is detected, the next step involves the approximate calculation of plant size using height measurement algorithms in 2D images, for detection convolutional neural networks was applied where 500 digital images of corn plants of toad variety with different states of growth and lighting were used , this set of images was divided into two subsets 80% for training and 20% for the test. In the case of the measurement algorithm, 100 images were used as a true ground for the calculation of the heights of maize plants